(untitled) (Marketing Journal, 2025)
This article analyzes the issues of improving digital corporate governance models in joint-stock companies based on international standards and national practices . The study examines the impact of OECD principles , ISO standards , and digital technologies (blockchain , artificial intelligence , electronic voting ) on corporate governance . Proposals have been developed to strengthen shareholder engagement , ensure corporate transparency , and enhance digital security . 710